Good morning, Vietnam [videorecording (DVD)] - Levinson, Barry; Markowitz, Mitch; Williams, Robin, 1951-2014; Whitaker, Forest (Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 2006)
Imported by the Army for an early morning radio show in Vietnam, disc jockey Adrian Cronauer (Robin Williams) blasts the formerly staid, sanitized airwaves with a constant barrage of rapid-fire humor and the hottest hits from back home. The G.I.'s love him, but the brass is up in arms.